2014
DOI: 10.1073/pnas.1402862111
|View full text |Cite
|
Sign up to set email alerts
|

FGF5 is a crucial regulator of hair length in humans

Abstract: Mechanisms that regulate the growth of eyelashes have remained obscure. We ascertained two families from Pakistan who presented with familial trichomegaly, or extreme eyelash growth. Using a combination of whole exome sequencing and homozygosity mapping, we identified distinct pathogenic mutations within fibroblast growth factor 5 (FGF5) that underlie the disorder. Subsequent sequencing of this gene in several additional trichomegaly families identified an additional mutation in FGF5. We further demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
118
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 45 publications
(36 reference statements)
0
118
0
1
Order By: Relevance
“…FGF5 plays an important role in the regulation of anagen-to-catagen transition and the control of human hair length202122. DKK2 encodes for a member of the family of dickkopf WNT-signalling inhibitors, which are reported to be secreted by dermal papilla cells Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FGF5 plays an important role in the regulation of anagen-to-catagen transition and the control of human hair length202122. DKK2 encodes for a member of the family of dickkopf WNT-signalling inhibitors, which are reported to be secreted by dermal papilla cells Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mutations within the FGF5 gene are associated with hair length in cats (Drögemüller et al, 2007;Kehler et al, 2007). Using a combination of whole-exome sequencing and homozygosity mapping, Higgins et al (2014) identified distinct pathogenic mutations within the human FGF5 gene in several additional trichomegaly families. FGF5 was also identified to be a crucial regulator of hair growth in humans.…”
Section: Introductionmentioning
confidence: 99%
“…This is evident by the striking phenotypic similarities between human congenital disorders caused by alterations in Fgf signaling and their corresponding mouse models. Conserved developmental requirements have been demonstrated in skeletal growth, palate closure, limb patterning, ear development, cranial suture ossification, neural development, and the hair cycle (Hebert et al 1994;Rousseau et al 1994;Shiang et al 1994;Wilkie et al 1995;Partanen et al 1998;Chen et al 1999;Li et al 1999;Wang et al 1999Wang et al , 2005Dode et al 2003;Tsai et al 2005;Gill and Tsai 2006;Mason 2007;Riley et al 2007;Falardeau et al 2008;Mansour et al 2009;Stanier and Pauws 2012;Simonis et al 2013;Higgins et al 2014;Ornitz and Marie 2015). These conserved developmental functions and accessible genetics make the mouse an excellent model for studying the mechanisms that Fgf signaling uses in vivo, which we discuss in this review.…”
mentioning
confidence: 99%